PENGARUH CONTENT MARKETING DAN INFLUENCER MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE WHITE TOMATO BY ATHENA PADA PENGGUNA TIKTOK GEN Z DI SURABAYA - Dimas Yovie Pryatmoko; Siti Aminah (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study is to analyze the effects of influencer and content marketing on the purchasing behavior of Athena's White Tomato product among Generation Z TikTok users in Surabaya. 105 respondents were included in the quantitative study using the eksplanatory research approach and the purposive sample technique. Data collection is done using an online questionnaire, and analysis is done using SEM-PLS software from SmartPLS. The study's findings indicate that both influencer and content marketing have a positive and significant impact on consumers' purchasing decisions. Digital marketing strategies based on social media are quite effective at attracting Gen Z, who are very active on TikTok.